PENERAPAN MODEL PEMBELAJARAN BERBASIS PERMAINAN EDUKATIF DALAM MENINGKATKAN MOTIVASI SISWA PADA MATA PELAJARAN SKI DI MAN 1 TABALONG - Hatmiah Hatmiah (CV. ADIBA ASIHA AMIRA, 2025)
Learning motivation is a crucial factor in enhancing students' understanding of a subject, including Islamic Cultural History (SKI). However, at MAN 1 Tabalong, many students are less motivated to learn SKI due to conventional and less interactive teaching methods. This study aims to analyze the implementation of educational game-based learning models in increasing students' motivation in SKI subjects. This research employs a qualitative method with a descriptive approach. Data were collected through observations, interviews, and questionnaires administered to students and SKI teachers at MAN 1 Tabalong. The data analysis technique includes data reduction, data presentation, and conclusion drawing. The study results indicate that implementing educational game-based learning models, such as role-playing, interactive quizzes, and historical simulations, significantly enhances students' interest, engagement, and willingness to learn further. Students become more enthusiastic about participating in learning activities and grasp Islamic history materials more easily. Moreover, this method also improves students' social skills and critical thinking abilities. In conclusion, educational game-based learning models effectively enhance students' learning motivation in SKI subjects at MAN 1 Tabalong. Therefore, this method can serve as an alternative for educators to create more engaging and interactive learning experiences